Cell-penetrating peptides - Methods and protocols - Carlo Alberto Redi (European Journal of Histochemistry, 2011)
Among the present day scientific frontiers, the researches on the cell-penetrating peptides has a special place since the scientific community has not yet reached a consensus even in the terminology on what we are referring to when we speak about cell-penetrating peptides studies. Thus, Prof. Ulo Langel (Dept. of Neurochemistry, Stockolm University, Stockolm, Sweden) rightly explain in a necessary preface that there are in use so many definition for the same things: protein transduction domain (PTDs), Trojan peptides, model amphipathic peptides (MAPs), membrane translocating sequences (MTS) that the best way to refer to all of these molecules is to call all of them cell-penetrating peptides, CPPs. Thus, there is a need for an accepted definition of CPPs.....